FAKTOR-FAKTOR PEMBENTUK PERILAKU PELANGGAN "PINNOCHIO" DI KUPANG - Maria Augustin Lopes Amaral; Selfiana Goetha; Engelbertus G. Ch Watu; Apryanus Fallo (Jurnal Manajemen, 2020)
Understanding why exaggerated negative word of mouth customers complain the way they do is important from theorical, managerial and public policy perspectives. This research try to answer customer negative WOM and desirable organizational outcomes, the possibility that customer might routinely exaggerate their consumption experience stories has been neglected. This research uses non-random sampling method (convenience sampling) in order to collect data. 138 people in Kupang were used as respondents. Data were collected using questionnaire (google form). This study uses SEM analyze to test the data. The result suggested consumer dissatisfaction and consumer vanting had effect toward exaggerated negative word of mouth, interactional justice and perceived tie had no effect toward exaggerated negative word of mouth. Keywords: word of mouth, exaggeration, negative word of mouth, consumer dissatisfaction, consumer venting